Characterizing inflammatory biomarkers in post-stroke seizure risk and outcome prognostication - Ethan Y. Wang; Shubham Misra; Jennifer Yan; Pei Yi Chook; Yuki Kawamura; Rachel Kitagawa; Jennifer A. Kim; Emily J. Gilmore; Adam de Havenon; Adithya Sivaraju; Lawrence J. Hirsch; Guido J. Falcone; et al. (PLoS ONE, 2026)
Post-stroke seizures (PSS) are sequelae of intracerebral hemorrhage (ICH) that may negatively impact patient outcomes. Available literature suggests that inflammatory biomarkers contribute to epileptogenesis as well as mortality. This retrospective cohort study aimed to elucidate the prognostic ability of CCL2, IL6, and IL8 in PSS development. ICH data were collected at Yale New Haven Hospital from 2014 to 2021. Plasma biomarker levels were measured via cytometric bead array. Patients with EEG-recorded epileptiform discharges, EEG-recorded seizures, or clinical seizures after ICH were defined as seizures and epileptiform discharges (SED), while those without were defined as non-SED. SED was further divided into early and late, occurring before and 7 days post-ICH, respectively. Additionally, we examined if biomarkers were associated with poor outcome (modified Rankin Scale score of 3–6) and mortality at 90, 180, and 365 days post-ICH. We conducted univariable and multivariable logistic regression analyses and reported the findings as Odds Ratio (OR) and 95% CI. We examined 172 patients with ICH, of whom 33 had early SED, 29 had late SED, and 110 had no SED. In univariable analyses, CCL2, ICH volume, diabetes, and lobar ICH were significantly associated with late SED, whereas NIHSS score at admission, ICH volume, and lobar ICH were significantly associated with early SED (p < 0.05). Lower CCL2 levels were independent predictors of late SED in multivariable analyses (OR 0.58; 95% CI 0.41–0.80, p < 0.001), but not of early SED. Additionally, we identified an independent association between higher CCL2 levels and 90-day mortality in multivariable analysis for the combined early and late SED cohorts (OR 1.87; 95% CI 1.03–3.37, p = 0.038). Additional studies investigating additional aspects of biomarkers, such as their temporal profile post-stroke within 24 hours or beyond 72 hours, are needed.